Acute Effect of Pistachio Intake on Postprandial Glycemic and Gut Hormone Responses in Women With Gestational Diabetes or Gestational Impaired Glucose Tolerance: A Randomized, Controlled, Crossover Study - Feng, Xiaohui; Liu, Haili; Li, Zhaoping; Carughi, Arianna; Ge, Sheng (Frontiers in Nutrition, 2019)
Long-term consumption of pistachio could potentially improves glucose homeostasis. Impaired postprandial glucose, insulin, glucagon-like peptide-1 (GLP-1) responses have been reported in Gestational diabetes mellitus (GDM) patients. The objective of this study was to evaluate the acute effects of two isocaloric test meals, 42g pistachios and 100g whole-wheat bread (WWB) on postprandial glucose, insulin, and gut derived incretin levels in Chinese women with gestational impaired glucose tolerance (GIGT) or GDM. Expected glucose and insulin responses were observed after WWB consumption. Isocaloric pistachio intake had minimal effect on blood glucose or insulin. In both GIGT and GDM patients, significant higher GLP-1 levels were observed at 60 or 90mins after pistachio compared to WWB intake. Significant lower gastric inhibitory polypeptide (GIP) levels were observed at 30 and 60mins in GDM patients or 120 min in GIGT patients after pistachio compared to WWB intake. In summary, isocaloric pistachio intake has significant lower postprandial glucose, insulin and GIP but higher GLP-1 levels compared to WWB. Our data suggest using pistachio as effective alternative to a low-fat, high-carbohydrate eating pattern to improve postprandial glucose, insulin and GLP-1 response in women with GDM and GIGT.